2021
DOI: 10.1111/1462-2920.15394
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial community structure and functionality changes in response to long‐term metal and radionuclide pollution

Abstract: Microbial communities are essential for a healthy soil ecosystem. Metals and radionuclides can exert a persistent pressure on the soil microbial community. However, little is known on the effect of long-term cocontamination of metals and radionuclides on the microbial community structure and functionality. We investigated the impact of historical discharges of the phosphate and nuclear industry on the microbial community in the Grote Nete river basin in Belgium. Eight locations were sampled along a transect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 82 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…Overall, it is clear that the physico-chemical environment imposes restrictions on the applied method, especially for in situ processes. Since uranium-contaminated sites or often co-contaminated with toxic metals ( Sitte et al, 2015 ; Boteva et al, 2016 ; Rogiers et al, 2021a ), in situ bioremediation necessitates the presence of multiple metal resistance mechanisms, which are often present in the indigenous microbial communities thriving in such contaminated sites ( Choudhary and Sar, 2015 ; Agarwal et al, 2020 ; Rogiers et al, 2021a ).…”
Section: General Implications For Technological Applicationsmentioning
confidence: 99%
“…Overall, it is clear that the physico-chemical environment imposes restrictions on the applied method, especially for in situ processes. Since uranium-contaminated sites or often co-contaminated with toxic metals ( Sitte et al, 2015 ; Boteva et al, 2016 ; Rogiers et al, 2021a ), in situ bioremediation necessitates the presence of multiple metal resistance mechanisms, which are often present in the indigenous microbial communities thriving in such contaminated sites ( Choudhary and Sar, 2015 ; Agarwal et al, 2020 ; Rogiers et al, 2021a ).…”
Section: General Implications For Technological Applicationsmentioning
confidence: 99%
“…This may, in part, be the consequence of soil organisms (invertebrate macrofauna, mesofauna and microorganisms) typically being thought to be relatively insensitive to radiation compared to other biota [ 10 , 11 ]. Some studies have reported effects on soil fauna at sites with high levels of natural radionuclides, including uranium mines [ 12 15 ]. However, it is likely that chemical toxicity rather than radiation dose is the cause of effects observed at such sites.…”
Section: Introductionmentioning
confidence: 99%
“…These elements must be mobilized from the soil matrix and absorbed by the roots in the form of metal ions (DalCorso et al 2014). Moreover, as one of the main drivers underlying soil microbial community change, metal elements may also exert persistent stress on soil microbial communities, thereby impacting belowground biodiversity that comprises up to a quarter of the Earth's species (Beattie et al 2018;Wagg et al 2019;Rogiers et al 2021). As any soil disturbance may disrupt microbial activity (Bissett et al 2013), understanding the responses of microbial communities to soil metal elements is a fundamental ecological issue for maintaining belowground biodiversity and ecosystem stability.…”
Section: Introductionmentioning
confidence: 99%
“…As the second genome of plants and facilitators of soil ecosystem change (Coban et al 2022;Zhang et al 2022), soil microbes dominate terrestrial soil habitats (Bardgett & van der Putten 2014;Bahram et al 2018). Furthermore, soil microbes afford primary functions for the formation and maintenance of soil structure and fertility (Bronick & Lal 2005;Rogiers et al 2021); thus, variations in the microbial community may lead to significant changes in soil ecosystems (Rogiers et al 2021).…”
Section: Introductionmentioning
confidence: 99%